ANALYSIS DISSOCIATIVE AMNESIA OF ELLY CONWAY’S IN THE FILM ARGYLLE USING SIGMUND FREUD’S THEORY - Aulia, Audi Yesyah; Sari, Artanti Puspita (Direktorat Riset dan Pengabdian kepada Masyarakat, Universitas Bina Darma, 2024)
Abstract: This research explores the portrayal of dissociative amnesia and the dynamics of the id, ego, and superego in the character of Elly Conway in the film Argylle using Sigmund Freud's psychoanalytic theory. The study aims to describe how dissociative amnesia is depicted in Elly's character and to analyze the development of her personality in terms of Freud's structural model of the psyche. This study applies the qualitative descriptive analysis method. The findings indicate that Elly Conway suffers from dissociative amnesia, characterized by memory loss and disconnection from her past, resulting from the repression of traumatic memories. The study also reveals the evolving dynamics between the id, ego, and superego in Elly's personality. Initially dominated by her superego, Elly faces significant internal conflicts as repressed id impulses emerge. However, as the story progresses, her ego begins to dominate, allowing her to mediate between the desires of the id and the moral constraints of the superego. This research contributes to the understanding of character development in film, particularly in characters with dissociative disorders, through the lens of psychoanalytic theory.